حضور الخمرة في شعر مظفر النواب دراسة بلاغیة (Journal of the College of Education for Women, 2019)
This research is a rhetorical study that sheds light on themeprominent of central identified as custom poet of MUDAFAR AL NAWABpolitical and national' that "wine "that themes which had a prominentpresence and intense in his poetry .and objective of this research is to detectthe aesthetic performance ALNAWABY in which he put to categorization"wine" ,through observation of manifestation the presence of winey. Andrelated scream the images and the meaning of talking semantics base tomove in the spaces of the text and have built our study on three topics: westarted The first research with lexicon russet in the processes of countingand analysis of the semantics wine in the office of the poet trying to revealthe relationship between the functions (alcohol-drunk-the cup-the inn} andthe implication of real and metaphorical, we have found that the poet hadstripped that function implications real worn semantics metaphor understandeach through context .while uncertainly surround each other and enduredmore than read .The second search and stood the main techniques stylistic followedby the poet in the recruitment of that inductions has been detected, including(addressing mode –repetition -intertextuality - juxtaposition- against me)revealed that techniques for the breadth of the presence of alcohol in thepoem, starting with titles of the poems through the occupation of the spaceof frequencies within the text and then extended bridges with other text ofgreatest poets through technology intertextuality and finally create center ofan internal struggle over, through correspond to me embodies the duality(dunk-not drunk) our research the third we had to stop with the images ofpoetry generated by the ecart at language double -speak wine reminded us ofdisplacement semantic composition and sound we have know in which theability of the poet,language in the formulation of new meaning createdimages with space as what gratitude Sophie and myself what is emotionaland what is realistic social.